A Comparative Study on Levels of hs-CRP and Lipid Profile in Prediabetic and Normal Population - Maneesh Bains; Satpal Aloona; Gurvinder Singh; Rajneesh Bains (Wolters Kluwer Medknow Publications, 2024)
This study aimed to compare high-sensitivity C-reactive protein (hs-CRP) and lipid profile levels between prediabetic and normal populations and explore correlations between hs-CRP and lipid profile in prediabetic individuals. The study was conducted among Group A comprising 75 prediabetic individuals, and Group B, which included 75 non-diabetic controls from the general population. Results showed that the mean hs-CRP level in Group A (1.717) significantly exceeded that of Group B (0.917) (p = 0.001). Pearson correlation analysis revealed significant positive linear relationships between hs-CRP and lipid profile parameters, indicating that as total cholesterol, triglycerides (TGs), high-density lipoprotein (HDL), and very low-density lipoprotein (VLDL) increased, hs-CRP also increased. A significant negative linear relationship was observed between hs-CRP and HDL. Moreover, a positive linear relationship existed between hs-CRP and glycemic parameters (fasting blood sugar (FBS), postprandial blood sugar (PPBS), and Glycated haemoglobin (HbA1c)). It is concluded that elevated hs-CRP, an inflammatory marker, correlated with dysregulated lipid profiles, and glycemic parameters, indicating its potential role in assessing inflammation in prediabetic individuals and its association with dyslipidemia and glucose metabolism.